PERWATAKAN TOKOH UTAMA DALAM NOVEL DIAN YANG TAK KUNJUNG PADAM KARYA SUTAN TAKDIR ALISJAHBANA - Hardi, Novri; Seli, Sesilia; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThis research background is motivated by the desire to find a character from the novel title Dian yang Tak Berkunjung Padam by Sutan Takdir Alisjahbana. The general problem in this research is "How does the main character in Dian yang Tak Kunjung Padam novel by Sutan Takdir Alisjahbana?. The general problem is limited by two sub-problems, that are personality and emotion of main character in the Dian yang Tak Berkunjung Padam novel by Sutan Takdir Alisjahbana. The purpose of this study is to describe two sub-problems, while this research is useful for researchers to increase knowledge and insight in analyzing the literary works, this research also can be used by teachers and students as a media of learning as well as materials for comparison. This theory used in this study relates to novels, characters, personality and emotions. This research uses descriptive method, qualitative resecrh form, and using behavioristic psychology approach. The source of research data is Dian yang Tak Kunjung Padam novel by Sutan Takdir Alisjahbana Sutan Takdir Alisjahbana. The data collecting of this research is documentary study technique. The data in this study are quotations of words, phrases, sentences containing the personality of the main character and the emotion of the main character. Â Key words: personality, emotion, psychology, novel